Dampak Brand Image, Harga, Dan Brand Trust Terhadap Keputusan Menggunakan Paket Umroh (Study Kasus Travel PT. Raya Al-Madinah Karangploso Malang) - Ilmatul Horijah; Nur Hidayati; Satria Putra Utama (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to determine and analyze the relationship between Brand Image, Price, and Brand Trust on the Decision to Use the Umroh Package Case Study at Travel PT. Raya Al-Madinah Karangploso Malang. In this study the method used to obtain data is to use a questionnaire. This research was conducted on customers of Travel Raya Al-Madinah, namely at the address Jl. Raya tanjung sari ruko kav 8 kepuharjo Karangploso Malang. East Java Postal Code 65152. Determining the number of samples in this study used